1985
DOI: 10.1148/radiology.157.3.3903856
|View full text |Cite
|
Sign up to set email alerts
|

Human fetal anatomy: MR imaging.

Abstract: Twenty-four pregnant women carrying 26 fetuses (two sets of twins) were imaged with magnetic resonance (MR) imaging at 0.35 T following sonographic evaluation. Each study was retrospectively evaluated to determine which of 33 normal fetal structures were visible on the images and which imaging parameters were most useful for depicting fetal anatomy. Fetal motion degraded fetal images in all but two cases, both with oligohydramnios and in the third trimester of gestation. Nevertheless, many fetal structures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Optimal spatial resolution was accomplished during the third trimester, although in one patient imaging was performed successfully at 25 weeks' gestational age. Consistent with earlier reports [16,18,20], the increased size of the brain and reduced fetal motion in the third trimester enhanced the use of MRI. Adequate sedation was achieved using intramuscular morphine sulfate, although several investigators have used intravenous diazepam [20] or fetal neuromuscular blockade with curare [4,6] or pancuronium bromide [16].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Optimal spatial resolution was accomplished during the third trimester, although in one patient imaging was performed successfully at 25 weeks' gestational age. Consistent with earlier reports [16,18,20], the increased size of the brain and reduced fetal motion in the third trimester enhanced the use of MRI. Adequate sedation was achieved using intramuscular morphine sulfate, although several investigators have used intravenous diazepam [20] or fetal neuromuscular blockade with curare [4,6] or pancuronium bromide [16].…”
Section: Discussionsupporting
confidence: 88%
“…Although several investigators have suggested that T2-weighted images produce high signal-to-noise ratios [16,17], in this series relative Tl-weighting with short echoes produced clear delineation between brain and cerebrospinal fluid [9,10,18,20]. Using these sequences, fetal motion artifact was reduced [20] and with the scan's capability to image in three orthogonal planes [9,10,20], cystic intracranial lesions such as Dandy-Walker cysts, porencephaly, or hydranencephaly were visualized clearly.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The application of MRI to fetal imaging has been limited because of artifacts resulting from the motion of the fetus. Fetal curarization and/or maternal sedation before the examination is usually needed to eliminate motion artifacts [11][12][13]. However, the recently developed fast scanning techniques provide clear images in single-breath hold without premedication [10,14,15].…”
Section: Discussionmentioning
confidence: 99%